2016
DOI: 10.1002/chin.201625052
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis of Novel Imidazo[1,2‐a]pyridine‐4‐hydroxy‐2H‐coumarins by Groebke—Blackburn—Bienayme Multicomponent Reaction as Potential NS5B Inhibitors.

Abstract: NS5B Inhibitors. -A Groebke-Blackburn-Bienayme three component reaction of 4-hydroxy-3-formylcoumarin, alkyl isocyanides, and 2-aminoazines is demonstrated to give various imidazo[1,2-a] fused heterocycles containing the coumarin scaffold. -(MANVAR, P.; SHAIKH, F.; KAKADIYA, R.; MEHARIYA, K.; KHUNT, R.; PANDEY, B.; SHAH*, A.; Tetrahedron 72 (2016) 10, 1293-1300, http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The ability of titled compounds to interact with protein was investigated by in silico screening against non-structural 5B (NS5B) viral protein. The hybrid coumarin derivative 105 interact with allosteric site of NS5B protein and exhibited a docked confirmation which was in good conformity with the reference ligand [79].…”
Section: Hybrid Coumarin Conjugatesmentioning
confidence: 82%
See 1 more Smart Citation
“…The ability of titled compounds to interact with protein was investigated by in silico screening against non-structural 5B (NS5B) viral protein. The hybrid coumarin derivative 105 interact with allosteric site of NS5B protein and exhibited a docked confirmation which was in good conformity with the reference ligand [79].…”
Section: Hybrid Coumarin Conjugatesmentioning
confidence: 82%
“…A Japanese research group led by Uchiumi et al demonstrated that naturally occurring 3-phenylcoumarins (3-PC) compounds (78,79), generally present in tea leaves suppress TPA-induced HIV promoter activity. These compounds did not show any suppressive effect on the cytomegalovirus (CMV) promoter, suggesting that they act specifically on the HIV promoter.…”
Section: /4-aryl Coumarinsmentioning
confidence: 99%